Au-dessus de tout soupçon ? L’entrée dans l’homosexualité de filles de migrants nord-africains - Laure Anelli (Genre, Sexualité et Société)
This article is based on a qualitative inquiry using sociological interviews with ten lesbian descendants of North African migrants, aged from 19 to 33 years and living in the Paris area. I show how the young women I met managed to by-pass the assignment to heterosexuality  produced by youth peers as well as by parents. We will see how the "forbidden" and pressure to marry work together to compel the girls to heterosexuality. They define two ages : before and after 25 years old. During adolescence, the denial of lesbianism, associated with the prohibition, allows homosexuality to be seen as an unexpected freedom. After 25 years old however, the situation of these girls' tends to be more complex. It appears that when they face competing social pressures, regarding forming a long-lasting couple and "coming out" from the lesbian environment and regarding mariage from the family - the young women respond by shaping the conditions for a sexuality "for themselves". They thus develop alternative and contrasting options.